âMONEY POLITICS DALAM PEMILU LEGISLATIF 2014â Studi Kasus Masyarakat Dusun Tunjungan, Desa Pengasih, Kabupaten Kulon Progo Daerah Istimewa Yogykarta - , HEROIK MUTAQIN PRATAMA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This study try to elaborate further on the presence of the practice of money politics in the 2014 legislative elections and also its implication to the vote result.Money Politics or the socalled âpolitik uangâ is not something new in the world of Indonesia electoral. However, the 2014 election of money politics is becoming increasingly massive and open to be done by any legislative candidates in every level to win the most votes. The focus of this study is to answer how the practice of money politics works in the legislative elections in 2014 in the resident Tunjungan village, Kulon Progo Regency and also the resulting electoral implications. Resident Tunjungan village is chose as the focus of this study with a view to limiting the study to be more focused and not widened.Because the research methods used in this study is a qualitative research method with a case study approach, which requires to be more elaborated bounderis deeper. This study will be supported by several theoretical frameworks related to money politics to answer the research question. The concept of money as political resources into early perspective in seeing how far the role of money in the process of getting power. Vote buying and pork barrel as two forms of money politics will be a conceptual framework to look at the political form of money, as well as how it works in the vote market in resident Tunjungan village. The results of this study indicate open proportional electoral system raises the possibility of competition between candidates to get a seat Legislative,and still made his money as a key victory in the candidate gets the most votes. Being the main background in the practice of money politics Resident Tunjungan Village.Besides the practice of money politics in the vote market in resident Tunjungan village has two forms and in a manner different works that vote buying by giving money amounting to Rp. 30,000, and the pork barrel to deliver the promise of construction of public facilities in the resident Tunjungan village.However both these forms always utilize liaison agent from the local elite resident Tunjungan village.While the final outcome of the vote in the resident Tunjungan village show candidates who use money politics occupies the highest vote totals in comparison to other candidates.